Economic evaluations of adult male circumcision for prevention of heterosexual acquisition of HIV in men in sub-Saharan Africa: a systematic review. - Olalekan A Uthman; Taiwo Aderemi Popoola; Mubashir M B Uthman; Olatunde Aremu (PLoS ONE)
Background There is conclusive evidence from observational data and three randomized controlled trials that circumcised men have a significantly lower risk of becoming infected with the human immunodeficiency virus (HIV). The aim of this study was to systematically review economic evaluations on adult male circumcision (AMC) for prevention of heterosexual acquisition of HIV in men. Methods and findings Studies were identified from the following bibliographic databases: MEDLINE (Ovid), EMBASE (Ovid), Cochrane Library (Wiley's internet version), NHS EED and DARE Office of Health Economics HEED. The searches were conducted in November 2009. The Drummond 10-point checklist was used for methodological critique of the economic evaluations. Cost data were inflated and converted to 2008 US dollars (US$). Of 264 identified papers, only five met the inclusion criteria and were included in the review. The studies were published between 2006 and 2009. Most of the studies were carried out from the perspective of government healthcare payer. The time horizon ranged from 10 to 20 years. All studies reported that AMC is cost-effective. The reported cost per HIV infection averted ranged from US$174 to US$2808. The key driver of the cost-effectiveness models was circumcision efficacy. Conclusions All published economic evaluations offered the same conclusion that AMC is cost-effective and potentially cost-saving for prevention of heterosexual acquisition of HIV in men. On these grounds, AMC may be seen as a promising new form of strategy for prevention of HIV and should be implemented in conjunction with other evidence-based prevention methods.